Binocular Perception of 2D Lateral Motion and Guidance of Coordinated Motor Behavior. (April 2016) - Fath, Aaron J.; Snapp-Childs, Winona; Kountouriotis, Georgios K.; Bingham, Geoffrey P.
Zannoli, Cass, Alais, and Mamassian (2012) found greater audiovisual lag between a tone and disparity-defined stimuli moving laterally (90–170 ms) than for disparity-defined stimuli moving in depth or luminance-defined stimuli moving laterally or in depth (50–60 ms). We tested if this increased lag presents an impediment to visually guided coordination with laterally moving objects. Participants used a joystick to move a virtual object in several constant relative phases with a laterally oscillating stimulus. Both the participant-controlled object and the target object were presented using a disparity-defined display that yielded information through changes in disparity over time (CDOT) or using a luminance-defined display that additionally provided information through monocular motion and interocular velocity differences (IOVD). Performance was comparable for both disparity-defined and luminance-defined displays in all relative phases. This suggests that, despite lag, perception of lateral motion through CDOT is generally sufficient to guide coordinated motor behavior.